Phytochemical and Nutritional Quality Changes During Irrigation and Postharvest Processing of the Underutilized Vegetable African Nightshade - Sivakumar, Dharini; Phan, Anh Dao Thi; Slabbert, Retha M.; Sultanbawa, Yasmina; Remize, Fabienne (Frontiers in Nutrition, 2020)
Underutilized or traditional leafy vegetables are grown in the wild and cultivated. They are consumed as nutritional accompaniments to staples, either raw (fresh), cooked, or in a dried form, through custom, habit, and tradition. These traditional leafy vegetables are natural rich sources of phytochemicals and nutritional compounds. Over time, the keenness for consumption of traditional vegetables has become less popular. Poor nutrient diets are the main cause of mortality and morbidity, especially in developing countries, where the problem is predominant due to poverty. Consumption of traditional vegetables can assist in the prevention of chronic disease development, as they contain various bioactive compounds that exhibit multiple health benefits. Traditional leafy vegetables play a vital role in combatting hunger, food insecurity, and malnutrition, and most are suitable for food intervention programs. African nightshade (Solanum family) is one such commonly consumed traditional leafy vegetable. During dry seasons, communities often face shortages of vegetables; thus, the preservation of edible leaves is one strategy to help overcome this problem. The adoption of solar drying and fermentation are traditional methods to extend the availability of African nightshade vegetables. Additionally, the agronomy practices and postharvest processing methods affect the phytochemicals and nutritional compounds of African nightshade accessions. This mini-review provides information on changes in phytochemicals, nutrition, and antinutritive compounds with different postharvest processing methods and irrigation. The review provides the justification to promote the cultivation for consumption, by identifying the potential African nightshade accessions that are rich in phytonutritional compounds. This mini-review summarizes and discusses the major information on (i) the micro- and macronutrients present in Solanum retroflexum, the most commonly consumed nightshade species compared with other traditional vegetables in Southern Africa, (ii) the composition of phytochemical compounds present in different nightshade accessions, (iii) the impact of irrigation on phytochemical composition in different nightshade species, and (iv) the impact of postharvest processing on phytochemicals and antinutritive compounds in S. retroflexum. Inclusion of African nightshade, especially S. retroflexum, with the main staple foods can improve protein, iron, and calcium levels in daily diets, which will help to improve people's health and well-being.